Do Trait Emotional Intelligence and Dispositional Mindfulness Have a Complementary Effect on the Children’s and Adolescents’ Emotional States? - Mestre, Jose M.; Turanzas, Jorge; García-Gómez, Maria; Guerra, Joan; Cordon, Jose R.; De La Torre, Gabriel G.; Lopez-Ramos, Victor M. (Frontiers in Psychology, 2019)
Mindfulness is both a non-judgmental and present-centred awareness, which has been applied to reduce negative emotions. However, Trait Emotional Intelligence (TEI) is how well people perceive their emotional intelligence abilities (perceiving, expressing, understanding, and regulating emotions), which are involved in in people’s social functioning. This empirical study was designed to analyse whether dispositional mindfulness (DM) and TEI have a potential combined role for children and adolescent’s emotional states. In a sample of primary school students (N=318), age ranged from 8 to 16 years old (M= 11.25, SD=2.20), participants completed a TEI measure (ESCQ, Emotional Skills and Competence Questionnaire) and two measures of DM (CAMM, Child and Adolescent Mindfulness Measure and AFQ-Y, Avoidance and fusion questionnaire for youth).The criteria measures selected were: PANAS (Positive affect and negative affect schedule), White Bear Suppression Inventory (a thought suppression inventory), and STAIC (State-Trait Anxiety for Children). Findings indicated that TEI measures (labelling and expression, understanding, and managing emotions) were positive and significantly related with positive emotional states (especially, positive affect and balance) and negatively, with a lower association, with state anxiety. However, DM measures were both negatively and strongly associated with negative emotional states (thought suppression, negative affect, and anxiety). The conclusions indicate that a combined effect of both TEI skills and DM based interventions would be more complete than each one separately for a better social functioning of children and teenagers.